Three failure modes of High-Strength Steel (HSS) perfobond connector embedded in UHPC. (1st July 2023) - Liu, Yangqing; Yang, Haiyan; Luan, Liujie; Xu, Xiaoqing; Liu, Yuqing; Du, Xiaoqing
Highlights: Three failure modes of HSS perfobond connectors embedded in UHPC were found in the push-out test. The effects of hole diameters, plate thicknesses, and steel grades on the transition condition of failure modes were investigated. An analytical model for the shear capacity of PBLs considering the varying failure modes was proposed, which matched well with the 90 parametric study results. Abstract: The application of advanced high-performance materials, such as High-Strength Steel (HSS) and Ultra-High Performance Concrete (UHPC), provides innovative concepts for structural designs. To implement lighter, longer-span, and more durable structures, composite structures consisting of HSS and UHPC have been paid more attention recently since their combination might fully develop the superiority of each. Although perfobond connectors (PBLs) were reported to have excellent behavior, most studies focused on the PBLs with conventional materials and dimensions. The failure modes of PBLs with a smaller size embedded in UHPC are unclear. Besides, the current interface design methods are for ordinary composite structures, which could cause an unconservative design for HSS-UHPC composite structures. In this study, the push-out tests of HSS-UHPC PBLs with varying plate thickness and strength were performed. The fracture of perfobond plates, the fracture of perforated rebars accompanied by the yielding of hole walls, and the rebar fracture without hole wall yielding were found as the three failure modes. The failure mode significantly affected the shear strength and slip capacity, and the shear stiffness increased with the plate thickness. Then, the FE models that considered the fracture of perfobond plates and perforated rebars were established and validated. 90 numerical models with different hole diameters, plate thicknesses, and steel grades were built to investigate the transition conditions between the failure modes. Lastly, a shear capacity equation for PBLs considering the varying failure modes was proposed, which matched well with the parametric study results.